The impact of leadership style on turnover rates in the retail industry - Chan, Jia Min (2024)
The retail industry is a vast and complex sector of the economy that involves the sale of goods and services to consumers. It encompasses a wide range of businesses, from small independent shops to large chain stores and even online retailers. The retail industry is a vital part of the global economy, as it provides employment opportunities for millions of people worldwide and generates significant revenue. Retailers are responsible for sourcing, purchasing, and marketing products to consumers, and they play a crucial role in shaping consumer behavior and preferences. (Loh & et al, 2022) The retail industry has a rich history that can draw back in centuries. In the past, retail was primarily conducted through small independent shops, where customers would purchase goods directly from the shopkeeper. Over time, the retail industry evolved, and new technologies emerged that allowed for mass production and distribution of goods. The industrial revolution brought about significant changes in the retail industry, with the introduction of steam engines and mass manufacturing leading to the emergence of department stores. In recent years, there has been a growing focus on sustainability and ethical practices in the retail industry. (Loh & et al, 2022) Turnover rate is an important metric for organizations to track, and leadership can play a significant role in managing turnover. Measuring turnover rates can help organizations understand how many employees are leaving and why, which can inform decisions about recruitment, retention, and workforce planning. If an organization has a high turnover rate, it may indicate that there are issues with employee engagement, job satisfaction, or leadership that need to be addressed.(Stanek, 2019) Leadership can also play a role in managing turnover by creating a positive work environment, providing opportunities for growth and development, and addressing employee concerns and feedback. Results show from the previous research done by Schermuly et al (2022) psychological empowerment was moderately influenced by all of the positive leadership philosophies that we 2 evaluated. Leaders should be aware of the factors that contribute to turnover and take steps to address them, such as improving communication, providing recognition and rewards, and offering competitive compensation and benefits (Islam et al., 2018). Turnover rates make it important for leaders to focus on creating a positive work environment and addressing the factors that contribute to turnover (Pradhan et al., 2017). . By doing so, organisations can improve employee engagement and retention, which can lead to better business outcomes. This study aims to find out how leadership style affects the rate of employee loss in retail. With different ways to lead and how they affect employee happiness and engagement, we hope to shed light on the main factors that cause retail organisations to have high or low turnover rates. Through study and analysis, we hope to come up with useful insights and practical suggestions that retail leaders can use to create a positive and supportive work environment, cut down on employee turnover, and keep more employees overall. In this study, we'll look at the different types of leadership that are common in the retail business, such as transformational leadership, transactional leadership, and "let's just see what happens" leadership. Each style has its own ways to manage and motivate workers that are different from the others. By comparing the results of different types of leadership, we can get a full picture of how they affect turnover rates.The results of this study will not only add to what is known about leadership and employee turnover in the retail industry, but they will also give retail leaders actionable ways to improve their leadership skills and create a committed, engaged, and motivated workforce that wants to stay with the organisation. Ultimately, a better understanding of how leadership style affects turnover rates will help retail businesses build a strong and stable staff. This will help them grow and succeed in a market that is always changing.